Impact of Marble Powder on the Geotechnical Behavior of Expansive Soil - Hwayyiz, Chrakhan Amjed; Ahmed Mohammed Hasan; Hummadi, Rizgar Ali; Hawkar Hashim Ibrahim (Zanco Journal of Pure and Applied Sciences, 2023)
In geotechnical engineering, the process of changing the characteristics of weak or undesirable soils using waste materials has gained importance. Waste materials frequently involve waste and by-product minerals, such as marble powder, which were unethically obtained in Iraq and had harmful environmental repercussions. The aim of this study is to determine how marble powder affects the geotechnical features, including consistency limits, density, shear strength parameters and swelling characteristics of clayey soils in Erbil city. Different percentages of marble powder (6%, 12%, 18%, 24%, 30%, and 36%) were used to treat the expansive soil. The outcomes indicated that marble powder could enhance the geotechnical properties. It is advised to add 18% percentage of marble powder to improve the soil as an optimized amount.